Behavior of money demand in Colombia during the period 2000: I-2010: IV - Aguirre, Harold Stevens Ávila (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The article develops an econometric model to determine the behavior of money demand in Colombia using theoretical fundamentals as proposed by the monetarist side in the reformulation of the quantity theory of money, developed by Milton Friedman. We used for the estimation the OLS method and the sample took quarterly data from 2000: I to 2010: IV. We used as scale variables real GDP and opportunity cost of the interest rate of Term Deposit Certificates VNPI, as the approximate variable of price level is assumed the CPI.